YBa2Cu3O7 films grown onto SrTiO3 and YSZ substrates by chemical solution deposition of trifluoroacetates - Domínguez A.B. (2021)
This work was supported by the Proyectos Integrales Program from the CONCYTEC agency, project title “Fabricacion de placas superconductoras de YBaCuO” (Contract No. 018 -2020 – FONDECYT – BM). A Bustamante Domínguez and A. Osorio Anaya thank the Vice-Rector Office for Research and Postgraduate from the Universidad Nacional Mayor de San Marcos for supporting their projects B151301031 and B171301856 . 2 3 7